Associations between the thermal spring timing variability and atmospheric teleconnection patterns over the past six decades in Finland - Kaboli, Sadegh; Kankare, Ville; Haghighi, Ali Torabi; Uvo, Cintia Bertacchi; Kasvi, Elina (Elsevier BV, 2026)
The timing of the spring season in the boreal region is shifting under global warming, with profound impacts on ecosystems and hydrological processes. However, the mechanisms driving this transition and its considerable interannual variability are not well described, especially regarding the influence of large-scale atmospheric teleconnection patterns. This study examines the temporal variability of the observed thermal spring season across Finland, a boreal country warming faster than the global average. Key spring timing indices, including onset, end, duration, and growing season onset, were calculated and analyzed using high-resolution (1 km × 1 km) daily mean temperature data from 1961 to 2023. Spatial and temporal patterns were identified through Empirical Orthogonal Function (EOF) decomposition, and their associations with major atmospheric teleconnection patterns were examined. Results indicated that during the past six decades, the spring onset has advanced by 2–6 days/decade, with the most pronounced changes in the coastal and southwestern parts of the country. The duration of the spring season has extended by 3–6 days/decade in the northern areas and along the southwestern coast. The early spring onset was associated with a strong positive phase of the Arctic Oscillation (AO), and delayed spring end and growing season onset were linked to the positive phase of the East Atlantic–West Russia (EAWR) pattern. By contrast, an early growing season start was linked to the positive phase of the North Atlantic Oscillation (NAO). The duration of the thermal spring season showed a strong association with the Scandinavian (SCA) pattern.